Wind Power Potential over the World’s Deepest River Valley - Regmi, Ram P.; Maharjan, Sangeeta (Journal of Nepal Physical Society, 2017)
Wind power potential prevailing over the world’s deepest river gorge, the Kali Gandaki River Valley, located in the western trans-Himalaya region of Nepal, has been assessed and mapped at 1 km × 1 km horizontal grid resolution with the application of Weather Research and Forecasting (WRF) modeling system. The wind power potential maps cover 70 km × 70 km area, which encloses the very first and failed wind power project in the country and the Jomsom Airport at the center. The simulated wind characteristics compare well with the available observed wind characteristic. The wind power potential appears to vary from good to outstanding over 200 km2 area along the axis of Kali Gandaki River Valley. However, a detail long-term observation, numerical simulation as well as engineering examinations are desired to address abnormal valley wind characteristics for sustainable power production over the area. Journal of Nepal Physical Society Volume 4, Issue 1, February 2017, Page : 54-59